Cranial osteomyelitis : diagnosis and treatment - Akhaddar, Ali (Springer Nature, 2016)
This book is the first reference book covering exclusively all aspects of this challenging disease. It is designed to serve as a succinct appropriate resource for neurosurgeons, otorhinolaryngologists, neuroradiologists, researchers and infectious disease specialists with an interest in cranial infection. Cranial Osteomyelitis provides an in-depth review of knowledge of the management of skull osteomyelitis, with an emphasis on risk factors, causative pathogens, pathophysiology of dissemination, clinical presentations, neuroradiological findings and treatment modalities, medical and surgical. Sections on the prognosis and prevention of this illness are also included. The book will help the reader in choosing the most appropriate way to manage this challenging bone infection. In addition, it supplies clinicians and investigators with both basic and more sophisticated information and procedures relating to the complications associated with skull osteomyelitis. It also considers future areas of investigation and innovative therapeutic philosophies. The book is richly illustrated to provide readers with unparalleled access to a comprehensive collection of cranial osteomyelitis images (biological, clinical, neuroradiological, and surgical) taken directly from the author's collection and experience in the field.